Effect of Ni Substitution on Structural, Dielectric, and Ferroelectric Properties and Variation in Magnetocapacitance of Single-Phase Ba0.7Pb0.3TiO3 Ceramic. (1st April 2022) - Chavan, Sanjay. G.; Mane, Sagar. M.; Chavan, Sanjeev. D.; Dhumal, Swati. G.; Kolekar, Yesh. D.; Kulkarni, Shrinivas. B.; Tayade, Nishant T.; Shin, Jae Cheol; Salunkhe, Dadasaheb J.
Abstract : The present study demonstrates the influence of Ni substitution on the structural, dielectric, and ferroelectric properties of single-phase Pb-doped BaTiO3, that is, Ba0.7 Pb0.3 TiO3 (BPT) ceramic, and variations in the magnetocapacitance. The hydroxide co-precipitation method was employed to fabricate single-phase Pb-doped BaTiO3 and Ni-substituted Ba0.7 Pb0.3 TiO3, as Ba0.7 Pb0.3 TiO3 -(x)Ni for x = 0.05, 0.1, and 0.15. Rietveld refinement reflects the single-phase tetragonal crystal structure of pure Ba0.7 Pb0.3 TiO3 and at higher Ni concentrations, the detection of rhombohedral crystal symmetry of the NiO phase confirms the biphasic structure of the composite. The ferroelectric-paraelectric transition temperature decreased from 274 °C for pure Ba0.7 Pb0.3 TiO3 to 162 °C for the composite with a higher Ni concentration of x = 0.15. A drastic change in the typical ferroelectric (P-E) loop of Ba0.7 Pb0.3 TiO3 was observed with the substitution of Ni. The composite with a higher concentration had the highest value of the magnetodielectric coupling coefficient, MD (%) = −2.86. This study reflects an easy and useful approach to achieve two-order parameter coupling with doping of acceptor ions in the ferroelectric phase. This kind of material substantially plays a vital role in the advanced electromagnetic devices for futuristic applications.